The Effectiveness of Active Intermittent Anaerobic Exercise and Passive Intermittent Anaerobic - Paturusi, Achmad; Podung, Beatrix J.; Bawiling, Nancy (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to determine the type of exercise that has a more effective effect in increasing the maximum work capacity between active anaerobic exercises with passive anaerobic exercises after conducting research on 24 male students of the Department of Coaching Education (PKL) Faculty of Sport Sciences (FIK) Manado State University (Unima) in aged 17-19 years as samples. The sample was divided into 2 groups, each of 12 people, namely anaerobic exercise group with active and passive intermittent anaerobic training groups. Both types of exercise are carried out on an ergometer bicycle (Monark). Design of the study "Randomized control group pre-test and post-test design". Collecting instrument "Ergometer bicycle which is stated by the number of Watts". Analysis with paired observation pair t-test statistics and two independent sample t-tests. The results obtained in this study are as follows; (1) The first hypothesis, there is the effect of anaerobic training that is active later on to increase the maximum work capacity in the male students of the Department of Coaching Education (PKL) Faculty of Sport Sciences (FIK) Manado State University (Unima). (2) The second hypothesis is that there is an effect of passive anaerobic training on increasing the maximum work capacity of male students of the Department of Coaching Education (PKL) Faculty of Sport Sciences (FIK) Manado State University (Unima). (3) The third hypothesis, there are differences in the effect of active intermittent anaerobic training and passive intermittent anaerobic exercises on increasing maximum work capacity. However, from the results of different tests prove that active intermittent anaerobic training is more effective when compared to passive anaerobic training to increase maximum work capacity in male students of the Department of Coaching Education (PKL) Faculty of Sport Sciences (FIK) Manado State University (Unima).